FORMULATION AND ANTIBACTERIAL ACTIVITY TEST OF RAMBUTAN HONEY TOOTHPASTE AGAINST Streptococcus mutans - Euis Reni Yuslianti; Titta Hartyana Sutarna; Frita Ferlita Shafri Djohan; Amalia Hasna (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Dental caries and periodontal diseases are the most common diseases affecting the oral cavity. This can be prevented by maintaining oral hygiene. Toothpaste plays an important role in the reduction of plaque bacteria and inflammatory conditions. Rambutan honey has potential as a natural ingredient to make toothpaste with antibacterial and antioxidant properties owing to the presence of hydrogen peroxide and catalase enzymes, pH, osmolarity, and flavonoid content. The purpose of this study was to obtain a rambutan honey toothpaste formulation that effectively inhibits Streptococcus mutans growth. The laboratory experimental research method was used to combine CaCO3, glycerin, Na CMC, SLS, sodium benzoate, saccharin, menthol, and aquadest as the toothpaste base, which served as the control group. Subsequently, natural ingredients of rambutan honey at concentrations of 20%, 40%, and 60% were added to the toothpaste base to create rambutan honey toothpaste. The formulation of the rambutan honey toothpaste was followed by an antibacterial activity test using the Kirby Bauer method of disc diffusion, where the inhibition zones formed on Mueller Hinton Agar (MHA) medium were calculated. Data were analyzed using one-way and post hoc Tukey’s tests (p<0.05). The results showed that the formulation of rambutan honey toothpaste with a concentration of 60% had the greatest inhibition with 13.88±0.13 mm with a significant difference in each group (p = 0.000), so it can be concluded that rambutan honey toothpaste can inhibit the formation of Streptococcus mutans.  Keywords: antibacterial, formulation, rambutan honey, toothpaste, Streptococcus mutans